Migration, Race and Nationhood in Argentina. - Bastia, Tanja; vom Hau, Matthias (Journal of Ethnic & Migration Studies, 2014)
Argentina has been a country of immigration since the Republican period. Moreover migration has played a key role in the construction of Argentinian nationhood. This paper traces migration policies and official accounts of migration from the nineteenth century to the present day in order to analyse the role of migration in nation-making. We argue that migration policies and official accounts of migration have changed significantly over the last 150 years. Yet, at least until the most recent migration policy reforms, these changing representations of migrants indicated major continuities of nationhood—namely, the persistent construction of Argentina as a white nation of European descendants. By tracing changes in migration policies and discourses then and now, this article addresses the relative absence of comparative works linking ‘new’ and ‘old’ migrations in Argentina. The article also shows how a historical perspective on migration continues to be relevant for understanding the experiences of contemporary migrants. The final section identifies recent changes in migration policy and discusses whether they indicate a radical departure from previous understandings of nationhood.